Chatbot helpdesk design for digital customer service - Larasati, P D; Irawan, A; Anwar, S; Mulya, M F; Dewi, M A; Nurfatima, I (Applied Engineering and Technology, 2022)
A chatbot is a computer program based on AI (Artificial Intelligence), namely virtual robots that simulate conversations like humans. Customer service (CS) is one of the many parts of a company that will directly contact customers. Therefore CS is expected to be able to provide fast and appropriate responses to customer complaints and needs. Using AI technology, Chatbot can help or replace customer service duties because it can provide information and help customers' constraints precisely and quickly. A chatbot is currently widely used by middle and upper companies. H3I is a kind of Chatbot that serving all loyal customers and can be implemented in various messenger platforms such as WhatsApp, Line, and others. For gathering the information, the authors use interview, observation, literature study. Moreover, the Prototype model is used for the development of Chatbot. The result was made a Chatbot for WhatsApp that can be used for customer service.